2014
DOI: 10.1039/c4fo00164h
|View full text |Cite
|
Sign up to set email alerts
|

In vitrotransport and satiety of a beta-lactoglobulin dipeptide and beta-casomorphin-7 and its metabolites

Abstract: Understanding the digestive behaviour and biological activities of dairy proteins may help to develop model dairy products with targeted health outcomes including increased satiety and healthy weight maintenance. Caseins and whey proteins constitute over 95% of milk proteins with consumption of these proteins associated with increased satiety and a decreased prevalence of metabolic disorders. To investigate the in vitro digestive behaviour and satiety of dairy proteins at the intestinal epithelium, the in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…These data are in agreement with the conclusions of two previous reports showing that intact or partially digested dietary proteins may exert stronger effects on satiety hormone release compared to protein hydrolysates and synthetic peptides [29], and that dipeptides and tripeptides may be ineffective in altering CCK release from STC-1 cells [107]. Furthermore, as to the possible synergistic effects of amino acids with different side chains, it has been previously observed that a mixture of l-tyrosine, l-threonine and l-methionine induced a significant change of CCK release whereas a single amino acid of the mixture had no significant effects [108].…”
Section: Evidence Supporting a Role Of Bioactive Peptidessupporting
confidence: 93%
See 2 more Smart Citations
“…These data are in agreement with the conclusions of two previous reports showing that intact or partially digested dietary proteins may exert stronger effects on satiety hormone release compared to protein hydrolysates and synthetic peptides [29], and that dipeptides and tripeptides may be ineffective in altering CCK release from STC-1 cells [107]. Furthermore, as to the possible synergistic effects of amino acids with different side chains, it has been previously observed that a mixture of l-tyrosine, l-threonine and l-methionine induced a significant change of CCK release whereas a single amino acid of the mixture had no significant effects [108].…”
Section: Evidence Supporting a Role Of Bioactive Peptidessupporting
confidence: 93%
“…In detail, somatostatin contributes to reduce the gastric acid secretion and gastric motility and inhibits the secretion of multiple gastroentericand pancreatic hormones [111]. Finally, β-CM7 and its fragment FPGPI stimulated the CCK secretion from STC-1 cells in vitro, whereas smaller fragments (YP and GPI) did not [8,107].…”
Section: Evidence Supporting a Role Of Bioactive Peptidesmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore a recent study found that neither the BLG dipeptide YL nor beta-casomorphin-7 (YPFPGPI) could stimulate GLP-1 secretion (Osborne et al, 2014). Also, the highest induction of CCK-8 was in response to beta-casomorphin-7, followed by the metabolite (FPGPI) and trior dipeptides had no effect.…”
Section: Discussionmentioning
confidence: 97%
“…This study is a first report of the passage of food-derived hemorphins, i.e., exogenous hemorphins, through the intestinal as well as the BBB in vitro (Table 1 ). Information on the in vitro absorption of alimentary proteins or of well-defined peptide sequences derived thereof has been mainly garnered from tests with milk proteins ( 34 36 ), much less from tests with whey proteins ( 19 , 37 ), or lately from egg albumin ( 38 ) but this information was unknown for hemorphins. The tested peptide the closest in terms of structure to hemorphins, is endomorphine-1 for which a low permeability through a caco-2 cell monolayer was reported ( 39 ).…”
Section: Discussionmentioning
confidence: 99%